2023
DOI: 10.1039/d3dt00089c
|View full text |Cite
|
Sign up to set email alerts
|

Group 13 salphen compounds (In, Ga and Al): a comparison of their structural features and activities as catalysts for cyclic carbonate synthesis

Abstract: Many complexes based on group 13 elements have been successfully applied as catalysts for the synthesis of cyclic carbonates from epoxides and CO2 and to date these have provided some...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 72 publications
3
10
0
Order By: Relevance
“…With an interest in exploiting the potential catalytic properties of the heavier group 13 elements for the cycloaddition reaction, the same authors explored a range of group 13 complexes bearing a salphen ligand (Figure 1c). 7 This work demonstrates that the indium complexes were more active than those based on gallium/aluminum.…”
Section: ■ Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…With an interest in exploiting the potential catalytic properties of the heavier group 13 elements for the cycloaddition reaction, the same authors explored a range of group 13 complexes bearing a salphen ligand (Figure 1c). 7 This work demonstrates that the indium complexes were more active than those based on gallium/aluminum.…”
Section: ■ Introductionmentioning
confidence: 76%
“…The approach to the synthesis of the group 13 complexes (aluminum, gallium, and indium) was similar to that of our previous report on group 13 salphen complexes. 7 Two approaches were used (Scheme 1); to obtain the aluminum compound with a chloride ligand, dimethyl aluminum chloride (AlMe 2 Cl) was directly reacted with the ligand (H 2 L) in an equimolar ratio, furnishing AlL-Cl. Meanwhile, all other complexes, ML-X (M = Al; X = Br.…”
Section: Synthesis and Characterization Of The Complexesmentioning
confidence: 99%
“…Due to involvement in the ring-opening or ring-closure stage, the ionic cocatalysts tetrabutyl-ammonium chloride (TBACl), tetrabutylammonium bromide (TBABr), or tetrabutylammonium iodide (TBAI) have been widely used in the cycloaddition of CO 2 with epoxides. Herein, we have studied the effect of TBACl, TBABr, TBAI, and tetrabutylammonium tetrafluoroborate (TBABF 4 ) on the Zn4- catalyzed coupling of CO 2 with 2-phenyloxirane, and the results (Table , entries 1–4) show the crucial role of anions in this reaction. Due to the expected participation of BF 4 – and Cl – anions in strong intermolecular charge assisted hydrogen bonding, both TBABF 4 and TBACl are not effective in the reaction, in contrast to weaker hydrogen bond acceptor and good leaving ability of Br – and I – in TBABr and TBAI, which can facilitate the ring-opening or ring-closure stage in the formation of cyclic carbonate. , Since TBABr appears to be an appropriate cocatalyst, it was used in further optimization experiments in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Donor solvent molecules are required for complex stabilization; attempts to synthesize 1a−c and 2a−c in noncoordinating solvents such as dichloromethane and benzene formed unknown decomposition products. Characterization of these complexes in solution using 1 H, 13 C, and 2D NMR spectroscopic techniques showed that all of the gallium complexes 1a−c are tetra-coordinate with two alkyl and two THF ligands (Figures S1−S12). The indium compounds showed more structural diversity in solution.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The handful of experimental or computational studies comparing the Lewis acidity of gallium and indium compounds focus only on the neutral species and come to conflicting conclusions about the relative Lewis acidity of these metals, making it difficult to compare the two metals directly. To the best of our knowledge, the comparative Lewis acidity of their cationic counterparts has not been examined to date. The majority of reported cationic group 13 complexes are supported by multidentate ancillary ligands. , The structural complexity of these ligands introduces variability, which often hinders a direct comparison of these compounds.…”
Section: Introductionmentioning
confidence: 99%